# Prove that `(1 + tan x)/(1+cot x) = tan x`

*print*Print*list*Cite

### 2 Answers

The identity `(1 + tan x)/(1 + cot x) = tan x` has to be proved.

`(1 + tan x)/(1 + cot x)`

=> `(1 + (sin x)/(cos x))/(1 + (cos x)/(sin x))`

=> `((cos x + sin x)/(cos x))/((sin x + cos x)/(sin x))`

=> `((cos x + sin x)/(sin x + cos x))*((sin x)/(cos x))`

=> `tan x`

**This proves that **`(1 + tan x)/(1 + cot x) = tan x`

(1+tanx)/(1+cotx) = (1+tanx)/(1+1/tanx)

= ((1+tanx)/[(1+tanx)/tanx]

= (1+tanx)(tanx)/(1+tanx)

= tanx